ANALISA PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA SEBAGAI ENERGI PENGGERAK POMPA MINYAK PADA STASIUN PENGISIAN BAHAN BAKAR UMUM DI KOTA DENPASAR - Juliawan, I Putu; Setiawan, I Nyoman; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 9 No 1 (2022): Jurnal SPEKTRUM, 2022)
Utilization of renewable energy as a source of electrical energy is an environmentally friendly energy development, one of which is the use of solar energy by developing solar PV on the roof of buildings as a medium for installing solar modules. In this study, a rooftop solar PV plan was carried out at the Nangka Utara gas station as a source of electrical energy which aims to reduce the cost of PLN electricity bills. The rooftop solar PV system at the Nangka Utara gas station uses an On-grid solar PV system without batteries, using 36 units of 415 Wp monocrystalline solar modules and one 15kW inverter unit. Planning for rooftop solar PV of the Nangka Utara gas station with a capacity of 14.9 kWp with the resulting energy production of 20.43 MWh per year. The initial investment cost required is IDR. 101.179,000 with a payback period of 5 years and 8 months.